2015
DOI: 10.3109/0886022x.2015.1077317
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products and soluble receptor as markers of oxidative stress in children on hemodialysis

Abstract: Background: Advanced glycation end products (AGEs) have biological properties that may contribute to the mortality of children on hemodialysis (HD). This study examines the relationship of LMW fluorescence AGEs, oxidized LDL (ox-LDL), soluble receptor AGE (sRAGE) as markers of oxidative stress in children with end stage renal disease (ESRD) undergoing HD. Method: Thirty children with ESRD undergoing HD, and 30 healthy, age-and sex-matched children were included. Serum levels of LMW fluorescence AGEs, sRAGE, ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…We also found a positive correlation between the AGEs level and sRAGE concentration in the AAA and HD patients, as well as in the CKD group. Our results are consistent with the observations made by El-Saeed et al, who demonstrated a positive correlation between the parameters mentioned above in children undergoing hemodialysis [40]. In general, the positive interrelationship between AGEs levels rather than the inverse relationship with sRAGE in humans, was observed [40,41].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also found a positive correlation between the AGEs level and sRAGE concentration in the AAA and HD patients, as well as in the CKD group. Our results are consistent with the observations made by El-Saeed et al, who demonstrated a positive correlation between the parameters mentioned above in children undergoing hemodialysis [40]. In general, the positive interrelationship between AGEs levels rather than the inverse relationship with sRAGE in humans, was observed [40,41].…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with the observations made by El-Saeed et al, who demonstrated a positive correlation between the parameters mentioned above in children undergoing hemodialysis [40]. In general, the positive interrelationship between AGEs levels rather than the inverse relationship with sRAGE in humans, was observed [40,41]. On the basis of the relationship mentioned above, we may conclude that AGEs stimulate the generation of sRAGE.…”
Section: Discussionsupporting
confidence: 93%
“…Longstanding hyperglycemia in type 2 diabetes is a major cause of corneal nerve loss and peripheral nerve injury, resulting from advanced glycation end products, disruptions of axonal function, uncontrolled oxidative stress and reactive oxygen species, and abnormal hemodynamic regulatory pathways [ 25 ]. Concurrent chronic kidney disease in type 2 diabetes worsens these abnormalities [ 26 , 27 ], facilitating a more severe corneal nerve loss. Furthermore, chronic kidney disease is closely associated with hyperkalemia, which may mediate nerve dysfunction in chronic kidney disease by altering nerve ion channel function [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the categorization of healthy volunteers into quartiles according to AGEs level revealed their effect on sRAGE concentration. The literature data show that serum levels of AGEs correlate positively rather than inversely with sRAGE [30,31]. Nevertheless, these correlations were elevated in pathological conditions, not in case of healthy subjects.…”
Section: Discussionmentioning
confidence: 99%